Investigation of Islamic Social Reporting, Public Ownership, Size and Firm Value: Testing the Mediation Effect of Financial Performance: JEL Classification: G32, G34, M14, Q56, Z12 - Rosmiati, Rosmiati; Hartono, Hartono; Santoso, Hadi (Newinera Publisher, 2025)
This study aims to analyze the influence of Islamic Social Reporting (ISR), public ownership, and firm size on firm value, with financial performance as a mediating variable, focusing on companies listed in the Jakarta Islamic Index (JII) on the Indonesia Stock Exchange (IDX). ISR serves as a crucial indicator for measuring corporate compliance with Sharia principles, encompassing social and environmental aspects. Research combining ISR with public ownership and firm size mediated by financial performance remains relatively rare in Indonesia. The study observes companies included in the JII, utilizing annual financial report data from 2019 to 2023. Path analysis is used to examine the relationships between variables through 10 research hypotheses. The analysis results indicate that ISR and public ownership (KPP) do not influence firm value (Tobin’s Q, TBQ). Meanwhile, firm size (SIZ) negatively affects financial performance (KJK) and TBQ. In the second model test, KJK appears to positively affect TBQ, while ISR shows a negative effect on TBQ. Furthermore, the Sobel test results reveal that KJK can only mediates the effect of SIZ on TBQ. Mediation effects of KJK on TBQ are not observed for ISR and KPP. These findings confirm that ISR directly affects TBQ. The negative impact of ISR needs further investigation, as it is inconsistent with theoretical concepts.